Exploring Semantic Mapping Strategy in Learning Vocabulary - Rahmawati, Ratini; Ahmad, Yousef Bani; Utami, Praditya Putri (Peneliti.net, 2024)
One of the main aspects that must be learned by English learners is vocabulary. In Indonesia, students' vocabulary knowledge is still low. It is because students do not learn vocabulary too deliberately in English classrooms. Semantic mapping strategy is one of the strategies for learning vocabulary that can develop students’ vocabulary. This study aims to explore semantic mapping strategy in learning vocabulary from students’ perceptions. The participants of this study were 9 students of 11th grade students of Islamic senior high school, five participants will be interviewed and the data will be analyzed qualitatively. The results showed that the students revealed positive perceptions in terms of emotions and attitudes. Most students felt semantic mapping is exciting and gave benefits for them such as can recall their past vocabulary, and extend their vocabulary including giving them knowledge of the word classes. However, there were also some students who have negative emotions and attitudes toward semantic mapping, but the emotions and attitudes of students are more towards the positive.